5 jaar Galerie-T. - Aletrino, H. P.; Blok, Cor; Duister, Frans; Juffermans, Jan; Kelk, Fanny; Steehouwer, Hein; Tegenbosch, Lambert; Wingen, Ed (Haarlem : Galerie-T, 1981)
Abram, Ronald ; Basart, Paul ; Biasi, Guido ; Constant ; Corneille ; Flor, Eduard ; Gaïtis, Yannis ; Gamarra, Jose ; Guidot, Raymond ; van Heusden, Wouter ; Hiraga, Key ; Klink, Age ; Krasno, Rodolfo ; Lanati, Luciano ; Maccio, Romulo ; Macréau, Michel ; Marcos, Alejandro ; Meckseper, Friedrich ; Miralda, Antoni ; Montijn, Jan ; Oudshoorn, Frank ; Peeter, Zoltin ; Sarri, Sergio ; Segui, Antonio ; Spermon, Kees ; de Spirt, Rolf ; Tajiri, Shinkichi ; Uota, Motoo ; Vanarsky, Jack ; Velickovic, Vladimir ; Verberk, John ; de Vries, Leo ; Wiesman, Hans ; Zekveld, Jacob ; Zuyderland, Siet
biog. per kunstenaar
Nederlands & Duits & Engels & Frans
boek